Deep Brain Stimulation Frequency of the Subthalamic Nucleus Affects Phonemic and Action Fluency in Parkinson’s Disease - Valéria de Carvalho Fagundes; Carlos R. M. Rieder; Aline Nunes da Cruz; Bárbara Costa Beber; Mirna Wetters Portuguez (Parkinson's Disease)
Introduction. Deep brain stimulation of the subthalamic nucleus (STN-DBS) in Parkinson’s disease (PD) has been linked to a decline in verbal fluency. The decline can be attributed to surgical effects, but the relative contributions of the stimulation parameters are not well understood. This study aimed to investigate the impact of the frequency of STN-DBS on the performance of verbal fluency tasks in patients with PD. Methods. Twenty individuals with PD who received bilateral STN-DBS were evaluated. Their performances of verbal fluency tasks (semantic, phonemic, action, and unconstrained fluencies) upon receiving low-frequency (60 Hz) and high-frequency (130 Hz) STN-DBS were assessed. Results. The performances of phonemic and action fluencies were significantly different between low- and high-frequency STN-DBS. Patients showed a decrease in these verbal fluencies for high-frequency STN-DBS. Conclusion. Low-frequency STN-DBS may be less harmful to the verbal fluency of PD patients.